Education is a black woman: escrevivência as an epistemological tool (Praxis Educativa, 2025)
This paper is written by black extensionist research professors who, taken from the literature of Conceição Evaristo, present the concepts of identity, language and memory, meanings performed by the epistemic/methodological tool of Escrevivência. In the black voices of all teachers, the principle of Escrevivência founds and reinvents practices in education. In this construction, the seminal figure of education is the black mother, as Lélia Gonzalez conceives her and as Conceição Evaristo presents as the principle of Escrevivência.
Keywords: Escrevivência; education; epistemology; black mother; black woman